Managing Openness and Volatility : The Role of Export Diversification - Haddad, Mona; Lim, Jamus Jerome; Saborowski, Christian (World Bank, Washington, DC, 2012)
As developing countries look to embrace an outward-oriented growth strategy, some may be concerned about the possibility that increased openness will be accompanied by increased volatility. However, although a more open economy may face increased volatility in its terms of trade, openness confers diversification benefits. In this note, authors argue that export diversification is a key mitigating factor for the total effect of openness on volatility. More specifically, authors show that most developing countries fall on the "good" side of a diversification threshold, where they are likely to experience less volatility as they pursue a strategy of greater openness.